Implementing the First Best in an Agency Relationship with Renegotiation: A Corrigendum - Edlin, Aaron S.; Hermalin, Benjamin E. (Econometrica, 2001)
The proof in Proposition 4 in Hermalin and Katz (1991) is incorrect because it fails to check post-renegotiation utilities against the incentive compatibility constraints. This note states and proves a comparable proposition witha slightly stronger assumption regarding the monotonicity of bargaining. This result vindicates the central intuition of Hermalin and Katz about the potential insignificance of the observable, but unverifiable distinction in contracting.